2011
DOI: 10.1038/ncomms1240
|View full text |Cite
|
Sign up to set email alerts
|

5-Hydroxymethylcytosine in the mammalian zygote is linked with epigenetic reprogramming

Abstract: The epigenomes of early mammalian embryos are extensively reprogrammed to acquire a totipotent developmental potential. A major initial event in this reprogramming is the active loss/demethylation of 5-methylcytosine (5mC) in the zygote. Here, we report on findings that link this active demethylation to molecular mechanisms. We detect 5-hydroxymethylcytosine (5hmC) as a novel modification in mouse, bovine and rabbit zygotes. on zygotic development 5hmC accumulates in the paternal pronucleus along with a reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
628
3
21

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 710 publications
(701 citation statements)
references
References 32 publications
36
628
3
21
Order By: Relevance
“…38 It likely acts through protection against hydroxylation of 5-methylcytosine by the Tet3 protein. 39 5-hydroxymethylcytosine is not recognized by Dnmt1 and thus, without this protection, maternal imprints can be subject to replication-dependent passive demethylation. Zfp57 is an oocytederived maternal factor involved in preimplantation maintenance of both paternal and maternal imprints at multiple loci such as the paternally methylated intergenic ICR (IG-DMR) within the Dlk1-Meg3 locus (Meg3 is also known as Gtl2) and the maternally methylated Mest, Peg3 and Snrpn ICRs (Figure 1).…”
Section: Imprint Maintenance In Early Embryosmentioning
confidence: 99%
“…38 It likely acts through protection against hydroxylation of 5-methylcytosine by the Tet3 protein. 39 5-hydroxymethylcytosine is not recognized by Dnmt1 and thus, without this protection, maternal imprints can be subject to replication-dependent passive demethylation. Zfp57 is an oocytederived maternal factor involved in preimplantation maintenance of both paternal and maternal imprints at multiple loci such as the paternally methylated intergenic ICR (IG-DMR) within the Dlk1-Meg3 locus (Meg3 is also known as Gtl2) and the maternally methylated Mest, Peg3 and Snrpn ICRs (Figure 1).…”
Section: Imprint Maintenance In Early Embryosmentioning
confidence: 99%
“…Two examples of enzymes that are thought to play a part in active DNA demethylation are growth arrest and DNA damage-inducible 45α (GADD45α) 42 and activation-induced deaminase (AID) 45 . More recently, in mouse eggs and early embryos, the TET enzymes have been shown to help active DNA demethylation by hydroxylating of methylated cytosine [46][47][48] . This active process leads to replication-independent changes in the levels of methylated cytosine in DNA.…”
Section: Histone and Dna Modificationsmentioning
confidence: 99%
“…Furthermore, a study of the DNA methylation pattern in human 3PN zygotes established that active demethylation of the paternal PN occurs post-fertilization in both c-IVF and ICSI [32]. In addition, recent studies have shown that the demethylation of paternal PN is induced by conversion from 5mC to 5hmC by ten-eleven translocation methylcytosine dioxygenases (TETs) [9][10][11]. Among TET proteins, TET3 is intensely expressed in oocytes and zygotes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was found that 5-methylcytosine (5mC) in the paternal genome is specifically converted to 5-hydroxymethylcytosine (5hmC) during the pronuclear stage [9][10][11]. Although these three studies were conducted in animals, we applied a similar approach in this study, using epigenetic divergence to determine the origin of mPN and fPN in abnormal human zygotes with 1PN and 3PN.…”
Section: Introductionmentioning
confidence: 99%